Observation in the Foreign Language Classroom: An Initial Process of Critical Reflection? - Branéz, Leonor Nora Fabián (The ESPecialist, 2014)
This paper presents a research that aimed to understand critically the practice of observation as a methodological tool for the development of critical reflection in the discipline Teaching Practice/Supervised Curricular Training in Foreign Language I in a Portuguese-Spanish Course, based on notes in diaries and reports produced by students at an observation training. Learning from observation and self-reflection on praxis enable apprentices to learn by practicing, in interaction with those who already have experience in teaching. The results show a preliminary reflection of participants in terms of criticism.